Long-term Infective Endocarditis Mortality Associated With Injection Opioid Use in the United States: A Modeling Study. (9th September 2020) - Barocas, Joshua A; Eftekhari Yazdi, Golnaz; Savinkina, Alexandra; Nolen, Shayla; Savitzky, Caroline; Samet, Jeffrey H; Englander, Honora; Linas, Benjamin P
Abstract: Background: The expansion of the US opioid epidemic has led to significant increases in infections, such as infective endocarditis (IE), which is tied to injection behaviors. We aimed to estimate the population-level IE mortality rate among people who inject opioids and compare the risk of IE death against the risks of death from other causes. Methods: We developed a microsimulation model of the natural history of injection opioid use. We defined injection behavior profiles by both injection frequency and injection techniques. We accounted for competing risks of death and populated the model with primary and published data. We modeled cohorts of 1 million individuals with different injection behavior profiles until age 60 years. We combined model-generated estimates with published data to project the total expected number of IE deaths in the United States by 2030. Results: The probabilities of death from IE by age 60 years for 20-, 30-, and 40-year-old men with high-frequency use with higher infection risk techniques compared to lower risk techniques for IE were 53.8% versus 3.7%, 51.4% versus 3.1%, and 44.5% versus 2.2%, respectively. The predicted population-level attributable fraction of 10-year mortality from IE among all risk groups was 20%. We estimated that approximately 257 800 people are expected to die from IE by 2030. Conclusions: The expected burden of IE among people who inject opioids in the United States is large. Adopting a harm reduction approach, including through expansion of syringe service programs, to address injection behaviors could have a major impact on decreasing the mortality rate associated with the opioid epidemic. Abstract : Using simulation modeling, we predicted that the population-level attributable fraction of 10-year mortality for endocarditis among people who inject opioids was 20%, and we estimated that approximately 257 800 people are expected to die from endocarditis by 2030.